PARTNERSHIP-BASED BUSINESS RESILIENCE MODEL FOR VILLAGE-OWNED ENTERPRISES (BUMDES) - Hamzah, Hamzah; Prasetyo, Bayu Dwi; Priatna, Angka; Timuriana, Tiara (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2025)
ABSTRACTThis study analyzes the optimal institutional model for supporting BUMDes business development in several sectors. This study uses the Multiple-Criteria Decision-Making (MCDM) approach with Interpretative Structural Modeling (ISM) as an analysis tool. Data was collected through interviews and focus group discussions with experts and stakeholders involved in BUMDes development. The study results indicate that the Village Government and Supervisors are the main driving factors in forming the BUMDes business ecosystem. BUMDes is the leading implementer of village businesses and is supported by various stakeholders. This partnership-based business resilience model emphasizes synchronization between the Village Head and BUMDes and the independence of BUMDes within the appropriate regulatory framework. Managerial implications include increasing BUMDe's professionalism, independence, strategic partnerships, and long-term planning. This study contributes to the BUMDes development literature by offering a holistic approach to analyzing the optimal institutional model in supporting BUMDes business growth.ABSTRAKPenelitian ini bertujuan untuk menganalisis model kelembagaan yang optimal dalam mendukung pengembangan bisnis BUMDes di beberapa sektor. Penelitian ini menggunakan pendekatan Multiple-Criteria Decision-Making (MCDM) dengan Interpretative Structural Modeling (ISM) sebagai alat analisis. Pengumpulan data dilakukan melalui wawancara dan focus group discussion dengan para ahli dan stakeholder yang terlibat dalam pengembangan BUMDes. Hasil penelitian menunjukkan bahwa Pemerintah Desa dan Pengawas merupakan faktor pendorong utama dalam membentuk ekosistem bisnis BUMDes. BUMDes berperan sebagai pelaksana utama usaha desa, didukung oleh berbagai pemangku kepentingan. Model ketahanan bisnis berbasis kemitraan ini menekankan sinkronisasi antara Kepala Desa dan BUMDes, serta kemandirian BUMDes dalam kerangka regulasi yang tepat. Implikasi manajerial meliputi peningkatan profesionalisme BUMDes, kemandirian, kemitraan strategis, dan perencanaan jangka panjang. Penelitian ini berkontribusi pada literatur pengembangan BUMDes dengan menawarkan pendekatan holistik untuk menganalisis model kelembagaan yang optimal dalam mendukung pertumbuhan bisnis BUMDes.